(untitled) (Journal of Engineering, 2026)
Rectangular gravity separators are commonly used within wastewater treatment systems to remove fat, oil, and grease from water. The performance of these vessels is dependent to a great extent on the uniformity of the flow, since turbulence and recirculating eddies tend to break drops together, thus reducing the separation efficiency. Therefore, adding the inlet baffle is a feasible way to improve the hydraulic stability in the separator. To simulate the characteristics of flow in the gravity separator tanks, a two-dimensional computational fluid dynamics (CFD) model of a single-phase flow has been developed with Flow-3D (v11.04). The numerical model employed was based on the Finite Volume Method (FVM), used the Volume of Fluid (VOF) technique to simulate the free surface behavior, and implemented an RNG k–ε turbulence model. Flow behavior was analyzed using three parameters: the velocity standard deviation, which denotes the flow uniformity, the percentage of recirculation zones corresponding to mixing and stability, and kinetic energy distribution. The results showed that the baffle with two apertures provided the best hydraulic performance by minimizing velocity fluctuations and cross-flowing and also kinetic energy distribution. Thus, this arrangement was determined to be the most effective design in promoting the flow stability and separation performance inside a rectangular gravity separator.